Olive Leaf Extract Supplementation to Old Wistar Rats Attenuates Aging-Induced Sarcopenia and Increases Insulin Sensitivity in Adipose Tissue and Skeletal Muscle - Daniel González-Hedström; Teresa Priego; Sara Amor; María de la Fuente-Fernández; Ana Isabel Martín; Asunción López-Calderón; Antonio Manuel Inarejos-García; Ángel Luís García-Villalón; Miriam Granado (MDPI AG, 2021)
Aging is associated with increased visceral adiposity and a decrease in the amount of brown adipose tissue and muscle mass, known as sarcopenia, which results in the development of metabolic alterations such as insulin resistance. In this study, we aimed to analyze whether 3-week supplementation with a phenolic-rich olive leaf extract (OLE) to 24 months-old male Wistar rats orally (100 mg/kg) attenuated the aging-induced alterations in body composition and insulin resistance. OLE treatment increased brown adipose tissue and attenuated the aging-induced decrease in protein content and gastrocnemius weight. Treatment with OLE prevented the aging-induced increase in the expression of PPAR-γ in visceral and brown adipose tissues, while it significantly increased the expression of PPAR-α in the gastrocnemius of old rats and reduced various markers related to sarcopenia such as myostatin, HDAC-4, myogenin and MyoD. OLE supplementation increased insulin sensitivity in explants of gastrocnemius and epididymal visceral adipose tissue from aged rats through a greater activation of the PI3K/Akt pathway, probably through the attenuation of inflammation in both tissues. In conclusion, supplementation with OLE prevents the loss of muscle mass associated with aging and exerts anti-inflammatory and insulin-sensitizing effects on adipose tissue and skeletal muscle.